Design of a modified atmosphere packaging for apple using concept of mathematical modeling for phytochemicals stability and shelf‐life enhancement. (31st January 2023) - Mangaraj, Shukadev; Thakur, Rajeev Ranjan; Nishad, Praween
Abstract: In the present investigation, experiments were conducted to model the rate of apple respiration at various temperatures using enzyme kinetics approach and Arrhenius equation. Thereafter, a governing mathematical model based on the mass balance concept was developed to design a modified atmosphere packaging (MAP) system for apple. The respiration rate model and developed equation employed in the MAP design process was verified and proved to be suitable, as indicated by moduli ( E  < 10%). Thereafter, a combination of biaxially oriented polypropylene (BOPP) and polyvinyl chloride (PVC) film having thickness of 30 and 50 μm, respectively was prepared by tailoring method to match the targeted gas permeability requirement of apple. The MAP system for apple was developed by packaging 1 kg of apple in the prepared film and the packages were stored at 2°C for further quality evaluation. The quality attributes of apple in terms of physico‐chemical properties, individual phenolic compounds, total phenolic content and total antioxidant capacity were assessed at a regular interval of time during storage. Based on physiological weight loss (<10%) and retention of other physicochemical and phytochemical quality till the end of storage period, the shelf life of apple was recorded as 180 days. Practical application: The lack of adequate cold storage systems in the supply chain, improper handling and storage facilities for fresh fruits including apple, is the leading source of post‐harvest loss of perishable commodity. The modeling of respiration rate at transient state and design of perm selective modified atmosphere packaging (MAP) system could be an alternative technology which can facilitate the shelf life enhancement of apple during handling and distribution. The uniqueness in the study involves the effect of MAP system on phytochemical compounds of whole apple during storage which has been rarely reported so far. The retention of overall quality of stored apple has proved that MAP is a promising technique for quality retention and achieving better market value.